Translanguaging in Nigerian and Malawian online newspaper readers' comments. Issue 2 (3rd April 2017) - Alimi, Modupe Moyosore; Matiki, Alfred Jana
ABSTRACT: The notion of language as a homogenous, stable and bounded system of communication has waned partly because of increased understanding of the language behaviour of bi/multi-linguals whose language use in different domains is now more appropriately described as translanguaging. The thrust of most definitions is that translanguaging involves the active engagement of language as an agent of making meaning using all the linguistic, cultural and social resources of users in particular instances of language use. This paper discusses translanguaging in online newspaper readers' comments on two specific stories in Nigerian and Malawian newspapers. The analysis reveals criticality and creativity as interactional strategies employed by participants when they co-act to adopt a point of view on national issues. Translanguaging, through the use of mixed forms and pidgin, featured prominently for casting aspersions or making derogatory remarks about political figures and government functionaries. Online forums also constitute a type of translanguaging space, for airing the collective voice of the populace on issues of national importance. We conclude that language practice in multilingual communities is complex and individuals rarely treat sets of linguistic features as complete, coherent and separated systems, but as resources for creating multilevels of social meaning.